Metastasis to spermatic cord from carcinoma prostate: A case series - Gahlawat, Sumit; Kabra, Sumit; Ahuja, Arvind; Sood, Rajeev; Sharma, Umesh; Goel, Hemant Kumar (Indian Journal of Case Reports, 2021)
Despite the high incidence of secondaries to lymph nodes, bones, and lungs in carcinoma (CA) prostate, metastatic involvement of scrotal organs is rare and usually associated with a poor prognosis. Here, we report a case series of three cases of CA prostate with metastatic involvement of scrotal organs. All three patients had metastatic involvement of the spermatic cord, with involvement of epididymis in the first patient and testes in the third patient, revealed incidentally on orchiectomy. Two patients were also found to have coexisting lymphatic filariasis. To date as per the best of our knowledge, only one such case of CA prostate with metastasis to scrotal organs and associated filariasis has been reported. This highlights the need for histopathological evaluation of all orchiectomy specimens. Chronic infection and inflammation leading to lymphatic obstruction due to filariasis probably led to the unusual retrograde spread of the tumor.